Formation sense of justice of minors. (Journal of actual problems of jurisprudence, 2016)
In article is considered приступность amongst minor. The Author the problems of the legal knowledges and her(its) infusing to minor. Also consider the question about warning of criminality minor.
Keywords: sense of justice formation efficiency